Economic Valuation of Environmental and Resource Costs - The Case of Germany - Benjamin Görlach; Eduard Interwies (European Regional Science Association (ERSA), 2005)
In the implementation of the EC Water Framework Directive, the concept of environmental and resource costs applies above all to the cost recovery of water services. Article 9 of the Directive stipulates that ,,Member States shall take account of the principle of recovery of the costs of water services, including environmental and resource costs." However, environmental and resource costs were not sufficiently defined in the Directive. In order to further clarify the concept of environmental and resource costs, and in order to discuss their assessment in practice, a European working group (DG Eco 2) was set up in September 2003. The paper "Economic Valuation of Environmental and Resource Costs: The Case of Germany” first summarises some of some main results of the DG Eco 2 working group. It then moves on to describe how environmental and resource costs are currently dealt with in Germany, and examines how the results of the DG Eco 2 can be put to use in the German context. A further point is the link between the assessment of environmental and resource costs and the selection of cost-effective combinations of measures. Two options are discussed here: first, addressing the question whether and how information obtained through the selection of measures can be used to assess environmental and resources costs; and secondly, discussing how the selected measures themselves can help to achieve cost recovery for environmental and resource costs. In this way, the results of the DG Eco 2 are linked to a previous research project, in which Ecologic developed a handbook for the cost-effective selection of measures under the WFD.
Keywords: 330